1995
DOI: 10.1111/j.1464-410x.1995.tb07259.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal enuresis

Abstract: Nocturnal enuresis is common. Although its aetiology remains unclear recent evidence increasingly supports the lack of a normal nocturnal increase in ADH leading to nocturnal polyuria exceeding functional bladder capacity. Sleep patterns are probably normal although an arousal disorder might be a factor. Treatment should follow careful evaluation to determine if one is dealing with 'uncomplicated' or 'complicated' enuresis. Complicated enuresis requires further investigation. 'Uncomplicated enuresis' always re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 43 publications
0
47
0
4
Order By: Relevance
“…25.4% of children wetted bed every night .This is marked evidence of bother though most of the children voided between 3and 10 times a month. Academic performance and emotional stability may be affected by enuresis 1,2 . Children have been proven to be socially maladjusted and emotionally unstable and academic performance adversely affected by enuresis in previous studies 1 Most studies have reported enuresis to occur frequently in children with a lower socioeconomic status 1,9 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…25.4% of children wetted bed every night .This is marked evidence of bother though most of the children voided between 3and 10 times a month. Academic performance and emotional stability may be affected by enuresis 1,2 . Children have been proven to be socially maladjusted and emotionally unstable and academic performance adversely affected by enuresis in previous studies 1 Most studies have reported enuresis to occur frequently in children with a lower socioeconomic status 1,9 .…”
Section: Discussionmentioning
confidence: 99%
“…10 In this study the presence of some comorbidities make enuresis polysymptomatic in 9.3% of enuresis. The polysymptomatic enuretic should be assessed thoroughly.Convulsions are an important factor in polysomatisation of enuresis 1,5,8 . 10% of children had epileptic convulsions and 2.6% had asthma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations